Excitation of surface wakefield in the dielectric waveguide without metal casing by the sequence of electron bunches - Kiselev, V.A.; Kirichenko, Yu.V.; Linnik, A.F.; Onishchenko, I.N.; Papkovich, V.G.; Pristupa, V.I. (Вопросы атомной науки и техники, 2013)
Results of theoretical and experimental studies of surface wakefield excitation in tubular dielectric tube without metal casing by a sequence of relativistic electron bunches were presented. The wakefield excitation in dependence of the transverse dimensions of the dielectric tube were investigated. The excited wakefield had the maximum amplitude at the optimum tube thickness, for which the bunch repetition frequency was equal to the frequency of the excited surface wakefield. Представлені результати теоретичних та експериментальних досліджень збудження поверхневих кільватерних хвиль в трубчатому діелектричному хвилеводі без металевого кожуха послідовністю релятивістських електронних згустків. Досліджені умови збудження кільватерного поля в залежності від поперечних розмірів діелектричної трубки. Кільватерне поле, яке збуджується в структурі, має максимальну амплітуду при оптимальній товщині трубки, при якій частота слідування згустків співпадає з частотою збуджуваної поверхневої хвилі. Представлены результаты теоретических и экспериментальных исследований возбуждения поверхностных кильватерных волн в трубчатом диэлектрическом волноводе без металлического кожуха последовательностью релятивистских электронных сгустков. Исследованы условия возбуждения кильватерного поля в зависимости от поперечных размеров диэлектрической трубки. Возбуждаемое кильватерное поле имеет максимальную амплитуду при оптимальной толщине трубки, для которой частота следования сгустков совпадает с частотой возбуждаемой поверхностной волны.